Sensitivity analysis of columns at extreme temperature - Al-Shayeb, Mohamed; Lie, T. T.; Abd. Ghani, Badri (Faculty of Mechanical Engineering, 1997)
This paper carried out a sensitivity analysis in order to know the effect of each parameters towards the mechanical strength of the protected column so that the results of this sensitivity analysis can be used to assist in the further research to increase the fire resistance. Among the parameters investigated are temperature, insulation thickness, load carrying capacity.